Older Drivers' Reasons for Reducing the Overall Amount of Their Driving and for Avoiding Selected Driving Situations. (April 2015) - Meng, Annette; Siren, Anu
Structured telephone interviews were conducted with 840 older drivers to explore their reasons for self-regulating their driving. The main reason for reduced driving was having fewer activities to drive to, and for avoidance of driving situations, reasons also included not liking or feeling insecure about driving in the situation. The lower-functioning participants, but still only a minority, were more likely to indicate decline in vision and reaction time as reasons for avoidance. Women were more likely to indicate lack of confidence as a reason for avoidance. The results suggest that the reduction in driving and avoidance of driving situations are separate types of self-regulatory behavior; that self-regulation of driving is an automatic process, in which older drivers are not aware that they are compensating for functional loss; and that it is important to acknowledge gender differences when designing interventions aimed at enhancing safe mobility.